2006
DOI: 10.1007/s000381-006-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Childhood’s gliosarcomas: pathological and therapeutical considerations on three cases and critical review of the literature

Abstract: In particular, they emphasize how modern diagnostic-therapeutic protocols make it possible to achieve a massive cytoreduction of the lesion in absolute safety in many cases, while avoiding further deficits in others, thus ensuring not only significant survival times but also a good quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…3,9,25 Previously, small series and a large population database study have demonstrated improved survival with adjuvant radiotherapy in patients with GS. 10,13,[20][21][22]24,30 Although our analysis is retrospective, it adds to the existing body of literature and suggests that the addition of chemotherapy to radiotherapy following tumor excision further improves survival.…”
Section: Discussionmentioning
confidence: 96%
“…3,9,25 Previously, small series and a large population database study have demonstrated improved survival with adjuvant radiotherapy in patients with GS. 10,13,[20][21][22]24,30 Although our analysis is retrospective, it adds to the existing body of literature and suggests that the addition of chemotherapy to radiotherapy following tumor excision further improves survival.…”
Section: Discussionmentioning
confidence: 96%
“…It usually occurs in elderly between 5 th and 6 th decades of life and extremely rare in paediatric population. Okami et al[ 5 ] reported eight cases of paediatric gliosarcoma, Sarkar et al[ 6 ] described three cases and Salvati et al[ 7 ] also reported three cases. Malde et al[ 8 ] reported one case of radiation induced gliosarcoma in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal lobe is most commonly involved followed by parietal and frontal lobe and can metastasize to extracranial structures like spinal cord, lung, pleura, liver, bone marrow and lymph nodes with increased frequency as compared to gliobastomas[ 7 ]. Pathogenesis of gliosarcoma is controversial topic and various studies have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Newly diagnosed pediatric GS typically occurs in cerebral hemispheres and is treated with total surgical resection, standard RT, followed by chemotherapy 3,4. Survival after total surgical resection without RT and chemotherapy is usually <6 months, but OS after RT and chemotherapy can extend to slightly over 2 years,3,4 making this case study’s report of OS and PFS of >13 years of significant clinical interest.…”
Section: Discussionmentioning
confidence: 87%
“…Survival after total surgical resection without RT and chemotherapy is usually <6 months, but OS after RT and chemotherapy can extend to slightly over 2 years,3,4 making this case study’s report of OS and PFS of >13 years of significant clinical interest. The benefit of TMZ has not yet been established 11.…”
Section: Discussionmentioning
confidence: 89%